ANALISIS POTENSI Chlorella Sp. DI PANTAI BASE-G SEBAGAI BAHAN BIODIESEL DENGAN UJI PROKSIMAT - Mishbach, Imam; Wanimbo, Efray; Rumbiak, Kristhopolus; Tuhumena, Lolita; Paiki, Kalvin (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Background: Phytoplankton is one of the microalgae that has great potential as an energy source, one of which is Chlorella sp.. Chlorella sp. is the largest producer of protein compared to other types of phytoplankton. The lipid and fatty acid content in microalgae is a source of energy that plays a role in the process of making biodiesel. Phytoplankton type Chlorella sp. easy to cultivate and breed. Supporting breeding in the process is supported by the use of fertilizers that are rich in nutrients so that it will optimize the growth of these phytoplankton. Generally fertilizer is divided into two, namely inorganic fertilizer and organic fertilizer. The aim of this research was to determine the fat content of Chlorella sp. which was obtained from the results of culture with the treatment of giving skipjack tuna fertilizer through a proximate test. Methods: This research was conducted by taking samples of Chlorella sp. At Base-G Beach. Samples were cultured and added liquid fertilizer from skipjack fish waste at a concentration of 4;8;12 ml/L. Chlorella sp. The culture results were calculated for cell density and tested for fat content through proximate fat analysis. Results: The study showed that the density of microalgae cells produced ranges from 0.21 x106 cells/ml to 0.51x106 cells/ml. The average proximate analysis of fat in microalgae was 0.022%-0.039% (w/w). The application of skipjack tuna waste fertilizer affected the proximate fat value of Chlorella sp. (p<0.05). Conclusion: The proximate fat content in Chlorella sp samples from Base-G beach which were cultured with the addition of liquid skipjack tuna waste fertilizer was 0.022-0.039% (w/w).